2003
DOI: 10.1080/110241598750005408
|View full text |Cite
|
Sign up to set email alerts
|

Benign tumour of the ampulla of vater: surgical treatment and prognosis

Abstract: Wide excision of the ampulla with reconstruction and reimplantation of the duct is adequate treatment for benign lesions. If the histological picture is uncertain, partial pancreaticoduodenectomy is justified in patients at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
1
19
1
5
Order By: Relevance
“…Dans notre travail, la mortalité nulle est conforme aux données récentes de la littérature [1,[8][9][10][11], mais contraste avec celle de 9 % rapportée dans le rapport de l'AFC de Marchal en 1978 [8]. Les progrès conjoints des techniques chirurgicales et de la prise en charge périopératoire permettent de proposer cette intervention à la condition d'une sélection préalable des malades.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dans notre travail, la mortalité nulle est conforme aux données récentes de la littérature [1,[8][9][10][11], mais contraste avec celle de 9 % rapportée dans le rapport de l'AFC de Marchal en 1978 [8]. Les progrès conjoints des techniques chirurgicales et de la prise en charge périopératoire permettent de proposer cette intervention à la condition d'une sélection préalable des malades.…”
Section: Discussionunclassified
“…Les progrès conjoints des techniques chirurgicales et de la prise en charge périopératoire permettent de proposer cette intervention à la condition d'une sélection préalable des malades. Il s'agit pourtant d'une intervention de moins en moins réalisée si l'on en croit les données de la littérature : 19 % des exérèses pancréatiques en 1978 contre 0 % pour des travaux plus récents [1,2,6,9,10]. La morbidité postopéra-toire n'est pas en cause pour expliquer ce phénomène.…”
Section: Discussionunclassified
“…In controlled, prospective studies, methods such as hypotonic duodenography [53], CT [9], magnetic resonance imaging (MRI), magnetic resonance cholangiopancreatography (MRCP) [2], and US [21,29] were significantly inferior to endoscopic diagnosis. Macroscopic appearance, site and size of the lesion, and tumoral stenosis can be visualized selectively using endoscopy, e.g., side view duodenoscopy (SVD) [33,34].…”
Section: Conventional Diagnostics In Adenomas Of the Papilla Vaterimentioning
confidence: 99%
“…Overstaging is reported to occur in as many as one third of T1 lesions [31], which is often due to inflammatory edema of the submucosa or from associated pancreatitis. EUS has been used as the most accurate way of identifying superficial tumors (adenomas and intramucosal carcinomas) suitable for local resection [59,64,31] and determining tumor stage prior to surgery [2,53,21,29,46,63,62]. Several studies have reported an overall accuracy rate of EUS of 78-90.6% [21,46,62,31,70].…”
Section: Advantages and Limitations Of Eus And Idus In Tumors Of The mentioning
confidence: 99%
See 1 more Smart Citation